Manipulation, and cryopreservation of autologous peripheral blood stem cell products in Italy: A survey by GITMO, SIDEM and GIIMA societies. (April 2020) - Lanza, F.; Mangianti, S.; Accorsi, P.; Lombardini, L.; Martino, M.; Saccardi, R.; Vassanelli, A.; Ostuni, A.; Ciceri, F.
Abstract: There is considerable heterogeneity in manipulation and cryopreservation of hematopoietic stem cells (HSC) for autologous HSC transplantation across Europe and Italy. To better address this point, three Italian Scientific Societies (GITMO- Gruppo Italiano per il Trapianto di Midollo Osseo; SIDEM- Società Italiana Emaferesi e Manipolazione Cellulare; and GIIMA- Gruppo Italiano Interdisciplinare Manipolazione e Aferesi per Terapie Cellulari), in collaboration with the Competent Authority "National Transplant Center" (CNT) sent to 85 Italian transplant centers (TC) a survey, which included 12 questions related to the most critical elements in graft processing. Fifty-nine centers (70 %) responded to the questionnaire. Overall, this survey demonstrates that the majority (>90 %) of responding TC used standardized procedures for HSC processing; however, an intercenter heterogeneity was clearly documented in several standard operating procedures adopted by different TC. These results seem to suggest that further standardization and efforts are needed to provide recommendations and guidelines on HSC manipulation, cryopreservation and functional assessment of cryopreserved material for autologous HSCT